2015
DOI: 10.1007/s10854-015-3272-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of annealing temperature on resistive switching behaviors of HfOx film

Abstract: The HfO x films annealed at different temperatures were fabricated. The crystal structure and chemical composition of the films showed strong dependence on annealing temperature. The prepared samples all exhibited bipolar resistive switching (RS) behavior. The results showed that the RS behaviors of HfO x sample in terms of ON/OFF ratio and endurance property can be improved by low temperature annealing process, while the ON/OFF ratio would be greatly reduced by high temperature annealing process due to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The inverse trend between μ h vs N t is also evident as shown in Figure c. From the literature, several reports showed that annealing at 200 °C yields optimal film quality and electrical properties, such as low defects, low leakage current, and an ultrasmooth film surface. ,, A similar trend can also be found in that lower annealing temperatures result in less charge trapping and interface states in oxides. , These findings are in accordance with our AFM and TFT results; the film quality and electrical properties were optimal at the lowest oxide annealing temperature (200 °C in this study). Moreover, AlO x was observed to show the lowest N t due to the smoothest surface, while HfO x was found to be in the opposite.…”
Section: Resultssupporting
confidence: 91%
“…The inverse trend between μ h vs N t is also evident as shown in Figure c. From the literature, several reports showed that annealing at 200 °C yields optimal film quality and electrical properties, such as low defects, low leakage current, and an ultrasmooth film surface. ,, A similar trend can also be found in that lower annealing temperatures result in less charge trapping and interface states in oxides. , These findings are in accordance with our AFM and TFT results; the film quality and electrical properties were optimal at the lowest oxide annealing temperature (200 °C in this study). Moreover, AlO x was observed to show the lowest N t due to the smoothest surface, while HfO x was found to be in the opposite.…”
Section: Resultssupporting
confidence: 91%
“…The device shifts into LRS state after capturing such electrons by the traps present on the interstitial sites of thin film specimen. [45] Here, for the positive bias voltage, the device is able to write and for the negative bias voltage, the device is able to erase so that the overall mechanism of memory device becomes polarity independent. [46][47][48] These overall features are sufficient to prove that fabricated WO 3 thin film-based Au/WO 3 /ITO memory device follows the unipolar resistive switching mechanism after annealing at 400 °C.…”
Section: Resultsmentioning
confidence: 99%